PC Cluster Possibilities in Mathematical Modeling in Quantum Mechanical Molecular Computations - Rakauskas, R. J.; Šulskus, J.; Vošterienė, S. (Nonlinear Analysis: Modelling and Control, 2002)
We present the PC cluster built in the Department of Applied Sciences of Lithuanian Military Academy. The structure of the cluster is described and the performance is evaluated by solving of linear algebra testing tasks and nonlinear quantum chemistry molecular electronic structure computations.